Upper Eyelid Contour Changes After Orbital Decompression in Graves Orbitopathy. Issue 3 (22nd November 2021) - Cruz, Antonio A. V.; Equitério, Bruna; Diniz, Stefania B.; Garcia, Denny M.; Rootman, Daniel B.; Goldberg, Robert A.; Galindo-Ferreiro, Alicia; Marqués-Fernández, Victoria; Sales-Sanz, Marco
Abstract : Purpose: To evaluate the effect of orbital decompression on the upper eyelid contour. Methods: A paired cross-sectional analysis of the upper eyelid contour was performed for 103 eyes of 66 patients who underwent orbital decompression. A control group of 26 normal subjects was also included. The eyelid contour of all participants were measured with Bézier lines adjusted to the eyelid contour and 9 midpupil eyelid margin (MPD) distances from a horizontal line bisecting the pupil. One central, corresponding to the margin reflex distance (MRD 1), and 8 equally distributed medially and laterally at 20% of the interval between the lines. Patients were classified as with flare if the height of the most lateral MPD relative to the MRD 1 was above the upper limit of the controls. Results: Preoperatively 63 of the 103 contours were classified as flare + (F+). After decompression MRD1 showed a mean decrease of 0.4 mm and the location of the contour shifted 0.8 mm medially. These changes were not correlated with proptosis reduction. Orbital decompression decreased the lateral curvature of the contours especially for the F+ lids. In 40% of the F+ eyelids the flare sign disappeared after decompression. Conclusions: Orbital decompression affects the lateral eyelid contour and diminishes the amount of lateral eyelid retraction surgery necessary to correct the flare sign. In 40% of the patients, the eyelid contour is normalized with proptosis reduction only. Abstract : Lateral upper eyelid retraction in graves orbitopathy is partially corrected by orbital decompression.